An in silico molecular dynamics simulation study on the inhibitors of SARS-CoV-2 proteases (3CLpro and PLpro) to combat COVID-19. Issue 14 (22nd September 2021) - Bera, Krishnendu; Reeda, V. S. Jeba; Babila, P. R.; Dinesh, Dhurvas Chandrasekaran; Hritz, Jozef; Karthick, T.
ABSTRACT: The work attempts to recognise the possible inhibitors against Papain-like protease (PL pro ) and 3-Chymotrypsin-like protease (3CL pro ) of SARS-CoV-2 to combat infectious COVID-19 virus using in silico studies. These two proteases are predominantly involved in the virus replication cycle; hence they are considered as potential drug targets. The virtual dock screening was performed for 53 selected drugs. The drugs with higher binding energy and oriented in the vicinity of active binding sites were selected for finding thermal stability using molecular dynamics (MD) simulation. The docking result reflects that the drugs A17 (Dasabuvir) and A34 (Methisazone) bind with PL pro and the drugs A17 and A53 (Vaniprevir) bind with 3CL pro with higher binding affinities. The MD simulation and principal component analysis show that the drug A17 has stable dynamic behaviour with both proteins over the 300 ns time-scale. The binding free energy of complexes was predicted from the last 100 ns trajectories using MM/PBSA. The predicted binding free energy of PL Pro -A17 (Dasabuvir) and PL pro -A34 complexes (Methisazone) were −16.1 kcal/mol and −12.3 kcal/mol, respectively and −41.3 kcal/mol and −11.9 kcal/mol for 3CL pro -A17 (Dasabuvir) and 3CL pro -A53 (Vaniprevir) complexes, respectively. However, further experimental validation is required to confirm their inhibitory activities against SARS-CoV-2 causing COVID-19.